Development of novel monoclonal antibodies for blocking NF-κB activation induced by CD2v protein in African swine fever virus - Fan, Rongrong; Wei, Zeliang; Zhang, Mengmeng; Jia, Shanshan; Jiang, Zhiyang; Wang, Yao; Cai, Junyu; Chen, Guojiang; Xiao, He; Wei, Yinxiang; Shi, Yanchun; Feng, Jiannan; et al. (Frontiers in Immunology, 2024)
Background CD2v, a critical outer envelope glycoprotein of the African swine fever virus (ASFV), plays a central role in the hemadsorption phenomenon during ASFV infection and is recognized as an essential immunoprotective protein. Monoclonal antibodies (mAbs) targeting CD2v have demonstrated promise in both diagnosing and combating African swine fever (ASF). The objective of this study was to develop specific monoclonal antibodies against CD2v. Methods In this investigation, Recombinant CD2v was expressed in eukaryotic cells, and murine mAbs were generated through meticulous screening and hybridoma cloning. Various techniques, including indirect enzyme-linked immunosorbent assay (ELISA), western blotting, immunofluorescence assay (IFA), and bio-layer interferometry (BLI), were employed to characterize the mAbs. Epitope mapping was conducted using truncation mutants and epitope peptide mapping. Results An optimal antibody pair for a highly sensitive sandwich ELISA was identified, and the antigenic structures recognized by the mAbs were elucidated. Two linear epitopes highly conserved in ASFV genotype II strains, particularly in Chinese endemic strains, were identified, along with a unique glycosylated epitope. Three mAbs, 2B25, 3G25, and 8G1, effectively blocked CD2v-induced NF-κB activation. Conclusions This study provides valuable insights into the antigenic structure of ASFV CD2v. The mAbs obtained in this study hold great potential for use in the development of ASF diagnostic strategies, and the identified epitopes may contribute to vaccine development against ASFV.